In vivo gene expression profiling for chemosensitivity to docetaxel-cisplatin-5-FU (TPF) triplet regimen in laryngeal squamous cell carcinoma and the effect of TPF treatment on related gene expression in vitro. (3rd July 2017) - Lian, Meng; Shi, Qian; Fang, Jugao; Feng, Ling; Ma, Hongzhi; Wang, Haizhou; Zhang, Liang; Wang, Hong; Ma, Zhihong; Liu, Honggang
Abstract: Conclusion: These results provided a battery of genes relating to TPF chemotherapeutic sensitivity and might act as molecular targets in laryngeal squamous cell carcinoma (LSCC) treatment. Moreover, these candidate biomarkers could contribute to LSCC individualized treatment. Objectives: To screen out a set of candidate genes which could help to determine whether patients with LSCC could benefit from TPF induction chemotherapy. Method: Gene-expression profiles in seven TPF-sensitive patients were compared to four resistant controls by microarray analysis. Subsequently, expression levels of potential biomarkers in chemosensitive cell line UMSCC5 after TPF treatment were observed by qRT-PCR. Results: Through microarray analysis, 1546 differently expressed genes were identified, of which 769 were up-regulated in TPF chemotherapy-responsive tissues, whereas 777 were down-regulated. Gene ontology (GO) analysis suggested these genes participating in physiological processes including cell differentiation, metabolism, signal transduction, and cellular component organization. Additionally, Kyoto Encyclopedia of Genes and Genomes (KEGG) database revealed that Wnt and p53 signaling pathways occupied important roles in TPF chemotherapeutic sensitivity. Moreover, in vitro cell culture experiments revealed the expression alternations of Mapk10, Jun, Vegfb, Pik3r5, Pld1, Tek, Itga6 exposed to TPF treatment by qRT-PCR, whilst providing an insight into the mechanism underlying TPF chemotherapeutic response in LSCC.